Mind the Gap : Addressing Critical Technical Issues in Strengthening National Hydrometeorological Services - Rogers, David P. (World Bank, Washington, DC, 2020)
This technical note is aimed primarily at professionals in national meteorological and hydrological services (NMHSs), who are trying to improve the quality and relevance of their services to match their societies’ growing needs for meteorological and hydrological information. At the same time, the note serves as a useful resource for the experts and teams involved in the activities and projects that tackle various aspects of transforming hydromet services. It provides insight into some of the technical challenges that NMHSs face and suggests approaches to addressing these challenges. The objective of this note is to bring attention to these technical issues to better understand them and prioritize the potential solutions.